The Development and Validation of the Feedback in Learning Scale (FLS) - Jellicoe, Mark; Forsythe, Alex (Frontiers in Education, 2019)
Research attention has shifted from feedback delivery mechanisms to supporting learners to receive feedback well (Winstone, Nash, Parker, & Rowntree, 2017). Recognising feedback and the action necessary to take the next steps are vital to self-regulated performance (Panadero, 2017; Zimmerman, 2000). Evaluative judgements supporting such mechanisms are vital forces that promote academic endeavour and lifelong learning (Ajjawi, Tai, Dawson, & Boud, 2018). Measuring such mechanisms is well developed in occupational settings (Boudrias, Bernaud, & Plunier, 2014). Understanding how these relate to self-regulated learning gains in Higher Education (HE) is less well understood (Forsythe & Jellicoe, 2018). Here we refined a measure of feedback integration from the occupational research domain (Boudrias et al., 2014) and investigate its application to HE. Two groups of psychology undergraduates endorsed perspectives associated with feedback. The measure examines process characteristics including message valence, source credibility, and challenge associated with feedback. Action characteristics including feedback acceptance, awareness, motivational intentions, and the desire to make behavioural changes and undertake development activities as a result of feedback. Exploratory factor analysis revealed that undergraduate learners endorsed a single process feedback factor, credible source challenge. From action characteristics, learners endorsed four factors. These include acceptance of feedback, awareness, motivational intentions. Finally, the desire to take behavioural changes and participate in development activities formed a single factor. The structure of the instrument and hypothesised paths between derived factors was confirmed using latent variable structural equation modelling. Both models achieved mostly good, and at least acceptable fit, endorsing the robustness of the measure in HE learners. These finding increase understanding of HE learners relationship with feedback. Here, acceptance of feedback predicts the extent to which learners found the source of feedback credible. Credible source challenge in turn predicts awareness resulting from feedback. Subsequently, awareness predicts motivations to act. These promising results, whilst cross-sectional, also have implications for programmes. Further research employing this instrument is necessary to understand changes in learner attitudes in developing beneficial self-regulated skills that support both programmes of study and graduates in their careers.